Paramilitary Policing In The Implementation of Police Departement Tasks : The National Police of the Republic of Indonesia (POLRI) - Simon R, A. Josias (International Journal of Criminology and Sociology, 2013)
This paper is the result of research that discusses the conception of paramilitary policing and investigating their implementation within the body of the POLRI. Including identify the elements of paramilitary policing in a variety of functional unit (satfung) in departement of police in resort level. The results of this study indicate the necessity of paramilitary policing control in the execution of duty serving the interests of the general public, but still needed internally in order to improve discipline and unity of police personnel in facing the instability and uncertainty of duties in the field. <!-- [if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->